Role of Treasury Single Account in Enhancing Transparency, Good Governance and Curbing Corrupt Practices in the Nigerian Public Service - Usman Sambo (Khazanah Sosial, 2023)
The Treasury Single Account (TSA) was introduced by the global international financial institutions specifically the World and IMF to help countries block leakages and other wastages that are associated with corrupt practices in the management of the public funds by the public servants. The TSA was embraced by the Nigerian Government with the same objective of blocking leakages and fostering transparency in public services. This has been behind the background of the allegations of corrupt practices, mismanagement, leakages, waste and squandering of public resources by the public servants who dubiously maintained several accounts for one ministry or agency. This study investigated the role played by TSA in the promotion of transparency, good governance, and preventing corrupt practices. The study used documented sources for assembling data involving the existing body of literature after thoroughly identifying the clear gap for contribution to knowledge. The sources obtained were discussed using empiricism where statistical data were analysed on the impact of TSA on preventing leakages and corrupt practices. The study discovered that the introduction of TSA in the Nigerian public service was a good reform and a success in minimising dubious transactions, corrupt practices, and the operation of suspicious redundant accounts by Ministries, Departments, and Agencies (MDAs) of Government. The study therefore, recommends that there is a need for full automation and digitalisation of governmental processes in Nigeria to reflect in other sectors of governance which can help in preventing leakages, malpractices, corrupt practices, and misgovernance.